Gender gaps in education: The long view1 - Evans David K. (Sciendo, 2021)
Many countries remain far from achieving gender equality in the classroom. Using data from 126 countries, we characterize the evolution of gender gaps in low- and middle-income countries between 1960 and 2010. We document five facts. First, women are more educated today than 50 years ago in every country in the world. Second, they remain less educated than men in the vast majority of countries. Third, in many countries with low levels of education for both men and women in 1960, gender gaps widened as more boys went to school, then narrowed as girls enrolled; thus, gender gaps got worse before they got better. Fourth, gender gaps rarely persist in countries where boys attain high levels of education. Most countries with large, current gender gaps in educational attainment have low levels of male educational attainment, and many also perform poorly on other measures of development such as life expectancy and GDP per capita. Fifth, in the youngest cohorts, women have more education than men in some regions of the world. Although gender gaps in educational attainment are diminishing in most countries, the empirical evidence does not support the hypothesis that reducing the gender gap in schooling consistently leads to smaller gender gaps in labor force participation.